2008
DOI: 10.1115/1.2812979
|View full text |Cite
|
Sign up to set email alerts
|

Blade Tip Clearance Flow and Compressor Nonsynchronous Vibrations: The Jet Core Feedback Theory as the Coupling Mechanism

Abstract: This paper investigates the role of tip clearance flow in the occurrence of nonsynchronous vibrations (NSVs) observed in the first axial rotor of a high-speed high-pressure compressor in an aeroengine. NSV is an aeroelastic phenomenon where the rotor blades vibrate at nonintegral multiples of the shaft rotational frequencies in operating regimes where classical flutter is not known to occur. A physical mechanism to explain the NSV phenomenon is proposed based on the blade tip trailing edge impinging jetlike fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…The above results point to the potential of widely used low-cost single-blade-passage computations, as done in this work, to predict rotating instabilities, mainly though the prediction of the occurrence of flow impingement. This type of simulation could then be combined with a model of flow oscillations associated an impinging jet, such as proposed in reference [19]. The resulting predictive tool would be of tremendous value to the gas turbine industry in the design of compressor and fan blades.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above results point to the potential of widely used low-cost single-blade-passage computations, as done in this work, to predict rotating instabilities, mainly though the prediction of the occurrence of flow impingement. This type of simulation could then be combined with a model of flow oscillations associated an impinging jet, such as proposed in reference [19]. The resulting predictive tool would be of tremendous value to the gas turbine industry in the design of compressor and fan blades.…”
Section: Resultsmentioning
confidence: 99%
“…This work has led to a simple and promising model and equation involving resonance of an impinging jet on a flexible surface to predict the speed at which NSV occurs [19].…”
Section: Resultsmentioning
confidence: 99%
“…Note that NSV of the compressor occurs at a stable operating condition and its frequency varies due to the mass flow, operating speed and temperature [19,5]. In addition, a URANS for the 1/7th rotor annulus with in-phase condition at the lower/uppper periodic boundaries were used for the NSV simulation in [4].…”
Section: Speedline Characteristicsmentioning
confidence: 99%
“…Tip clearance size is shown as the main influence parameter on the rotating instability. Thomassin et al [5,6] suggested a theory different from the rotating instability to explain the NSV based on the resonance of a impinging jet vortex structure and the acoustic feedback of a vibrating plate. The jet core feedback theory has been proved by an experiment conducted in [5,6].…”
mentioning
confidence: 98%